Electrocardiographic Findings in Brazilian Adults without Heart Disease: ELSA-Brasil - Pinto Filho,Marcelo Martins (2017)
Abstract Background: The electrocardiogram (ECG) is widely used in population-based studies. However, there are few studies on electrocardiographic findings in Latin America and in Brazil. The Brazilian Longitudinal Study of Adult Health (ELSA-Brasil) comprised 15,105 participants (35-74 years) from six Brazilian capitals. Objectives: To describe electrocardiographic findings in Brazilian adults without heart disease, stratified by sex, age and race/skin color. Methods: Cross-sectional study with baseline data of 11,094 adults (44.5% men) without heart disease from ELSA-Brasil. The ECGs were recorded with the Burdick Atria 6100 machine and stored at the Pyramis System. ECG analysis was automatically performed using the Glasgow University software. A descriptive analysis of heart rate (HR), P, QRS and T waves’ duration, PR and QT intervals, and P, R and T axes was performed. After stratification by sex, race/color and age, the groups were compared by the Wilcoxon and Kruskal-Wallis test at a significance level of 5%. Linear regression models were used to evaluate the behavior of electrocardiographic parameters over age. Major electrocardiographic abnormalities defined by the Minnesota code were manually revised. Results: Medians values of the electrocardiographic parameters were different between men and women: HR 63 vs. 66 bpm, PR 164 vs.158 ms, QT corrected 410 vs. 421 ms, QRS duration 92 vs. 86 ms, P-wave duration 112 vs. 108 ms, P-wave axis 54 vs. 57 degrees, R-wave axis 35 vs. 39 degrees, T-wave axis 39 vs. 45 degrees (p < 0.001 for all). The 2nd and the 98th percentiles of each variable were also obtained, and graphs were constructed to illustrate the behavior of the electrocardiographic findings over age of participants stratified by sex and race/skin color. Conclusions: The values for the electrocardiographic measurements herein described can be used as reference for Brazilian adults free of heart disease, stratified by sex. Our results suggest that self-reported race/skin color have no significant influence on electrocardiographic parameters.